Epigenetic regulation of Sox4 during palate development. (April 2013) - Seelan, Ratnam S; Mukhopadhyay, Partha; Warner, Dennis R; Webb, Cynthia L; Pisano, Michele; Greene, Robert M
Aim: Identification of genes that contribute to secondary palate development provide a better understanding of the etiology of palatal clefts. Gene-expression profiling of the murine palate from gestational days 12–14 (GD12–14), a critical period in palate development, identified Sox4 as a differentially expressed gene. In this study, we have examined if the differential expression of Sox4 in the palate is due to changes in DNA methylation.Materials & methods: In situ hybridization analysis was used to localize the expression of Sox4 in the developing murine secondary palate. CpG methylation profiling of a 1.8-kb upstream region of Sox4 in the secondary palate from GD12–14 and transfection analysis in murine embryonic maxillary mesenchymal cells using Sox4 deletion, mutant and in vitro methylated plasmid constructs were used to identify critical CpG residues regulating Sox4 expression in the palate.Results: Spatiotemporal analysis revealed that Sox4 is expressed in the medial edge epithelium and presumptive rugae-forming regions of the palate from GD12 to GD13. Following palatal shelf fusion on GD14, Sox4 was expressed exclusively in the epithelia of the palatal rugae, structures that serve as signaling centers for the anteroposterior extension of the palate, and that are thought to serve as neural stem cell niches. Methylation of a 1.8-kb region upstream of Sox4, containing the putative promoter, completely eliminated promoter activity. CpG methylation profiling of the 1.8-kb region identified a CpG-poor region (DMR4) that exhibited significant differential methylation during palate development, consistent with changes in Sox4 mRNA expression. Changes in the methylation of DMR4 were attributed primarily to CpGs 83 and 85.Conclusion: Our studies indicate that Sox4 is an epigenetically regulated gene that likely integrates multiple signaling systems for mediating palatal fusion, palatal extension and/or the maintenance of the neural stem cell niche in the rugae.